Mathematical model of engaging military interios troops units reserves definition with the operational situation in the area of their location and importance of the tasks in the area of duty - Poltorak, S. Т.; Babkov, Yu. P.; Batsamut, V. М. (Honor and Law, 2019)
Mathematical model of task for definition the operational plan for engaging the operational reserves of the internal forces in the case of occurrence several crises situations in several regions of the country has been improved. Also takes into consideration the priority areas of the duty, with transport charges to provide the march, the level of the operational environment in the areas of deployment military units. You can find example of solving the mentioned above goal.